ION CHANNELS: STRUCTURE AND THEIR ROLE IN CELLULAR FUNCTION (Web of Teachers: Inderscience Research, 2025)
Ion channels are integral membrane proteins that facilitate the selective transport of ions across cell membranes, playing a crucial role in maintaining cellular homeostasis and enabling physiological functions. This article explores the structural organization of various types of ion channels, highlighting their gating mechanisms and ion selectivity. It also examines the pivotal role ion channels play in processes such as electrical signal transmission in excitable cells, regulation of cellular volume, and intracellular signaling pathways. Furthermore, the article discusses the implications of ion channel dysfunction in the development of several diseases, emphasizing their significance as therapeutic targets. By providing an overview of ion channel structure and function, this study aims to enhance the understanding of their essential contribution to cellular physiology and their potential in medical research.